Human skeletal muscle hsp70 response to training in highly trained rowers - Liu, Y.; Mayr, S.; Opitz-Gress, A.; Zeller, C.; Lormes, W.; Baur, S.; Lehmann, M.; Steinacker, J. M. (Journal of Applied Physiology, 1999)
Previous studies have demonstrated exercise-induced heat shock protein 70 (HSP70) in animals. The purpose of this study was to investigate human skeletal muscle HSP70 response to rowing training. Ten male rowers trained for 4 weeks with different form, duration and intensity of exercise. Biopsy was performed in the right M. vastus lateralis before training and at end of each week. HSP70 in 5_g total protein from the muscle sample was determined using Western blot and immunodetection with chemiluminescence technique, by means of laser densitometer referring to a series of known standard HSP70. Compared to pre-training (100%), HSP70 increased during training (181%, 405%, 456% and 363% from the 1st to 4th training week, respectively) with the maximum HSP70 production at the end of 2nd training week. Thus, HSP70 is induced in highly trained human muscle by long-term training.